Homocystinuria patient and caregiver survey: experiences of diagnosis and patient satisfaction - Morrison, T; Bösch, F; Landolt, M A; Kožich, V; Huemer, M; Morris, A A M (Orphanet journal of rare diseases, 2021)
BACKGROUND: The main genetic causes of homocystinuria are cystathionine beta-synthase (CBS) deficiency and the remethylation defects. Many patients present in childhood but milder forms may present later in life. Some countries have newborn screening programs for the homocystinurias but these do not detect all patients. RESULTS: HCU Network Australia is one of the very few support groups for patients with homocystinurias. Here we report the results of its survey of 143 patients and caregivers from 22 countries, evaluating current diagnostic pathways and management for the homocystinurias. Most (110) of the responses related to patients with CBS deficiency. The diagnosis was made by newborn screening in 20% of patients and in 50% of the others within 1 year of the initial symptom but in 12.5% it took over 15 years. The delay was attributed mainly to ignorance of the disease. Physicians need to learn to measure homocysteine concentrations in children with neurodevelopmental problems, and in patients with heterogeneous symptoms such as thromboembolism, dislocation of the optic lens, haemolytic uraemic syndrome, and psychiatric disease. Even when the diagnosis is made, the way it is communicated is sometimes poor. Early-onset CBS deficiency usually requires a low-protein diet with amino acid supplements. More than a third of the participants reported problems with the availability or cost of treatment. Only half of the patients always took their amino acid mixture. In contrast, good adherence to the protein restriction was reported in 98% but 80% said it was hard, time-consuming and caused unhappiness. CONCLUSIONS: There is often a long delay in diagnosing the homocystinurias unless this is achieved by newborn screening; this survey also highlights problems with the availability and cost of treatment and the palatability of protein substitutes.
Keywords: novorozenec; Homocystinuria; Infant, Newborn; Patient Satisfaction; Patient support groups; Humans; Remethylation disorders; dítě; homocystinurie; Child; cystathionin-beta-synthasa; Cystathionine beta-Synthase; lidé; spokojenost pacientů; Caregivers; osoby pečující o pacienty; Patient reported outcome; Delay in diagnosis; Austrálie; Australia; Cystathionine beta-synthase deficiency